An infrequent cause of neonatal upper airway obstruction: Congenital nasal pyriform aperture stenosis presenting to a remote facility - Tahne Joseph Lahiff; Viliame Sotutu; Smrdhi Sarachandran; Lucas Speed; Vishal Saddi (Wiley, 2021)
ABSTRACT Introduction Congenital nasal pyriform aperture stenosis (CNPAS) is a rare congenital condition of structural nasal obstruction. Respiratory distress, stertor, and poor feeding are often presenting features. Case Presentation We report a case of a newborn diagnosed with CNPAS at 3 weeks of life. The diagnosis was missed on a nasoendoscopy at day 3 of life but was realised following a facial CT when the infant presented with ongoing symptoms of upper airway obstruction. Nasal dilation was performed successfully. Conclusion CNPAS should be considered in any neonate with upper airway obstruction. A normal nasoendoscopy does not exclude the diagnosis.